Species-Specific Expression of Growth-Regulatory Genes in 2 Anoles with Divergent Patterns of Sexual Size Dimorphism. Issue 1 (9th August 2022) - Cox, Christian L; Logan, Michael L; Nicholson, Daniel J; Chung, Albert K; Rosso, Adam A; McMillan, W Owen; Cox, Robert M
Synopsis: Sexual size dimorphism is widespread in nature and often develops through sexual divergence in growth trajectories. In vertebrates, the growth hormone/insulin-like growth factor (GH/IGF) network is an important regulator of growth, and components of this network are often regulated in sex-specific fashion during the development of sexual size dimorphism. However, expression of the GH/IGF network is not well characterized outside of mammalian model systems, and the extent to which species differences in sexual size dimorphism are related to differences in GH/IGF network expression is unclear. To begin bridging this gap, we compared GH/IGF network expression in liver and muscle from 2 lizard congeners, one with extreme male-biased sexual size dimorphism (brown anole, Anolis sagrei ), and one that is sexually monomorphic in size (slender anole, A. apletophallus ). Specifically, we tested whether GH/IGF network expression in adult slender anoles resembles the highly sex-biased expression observed in adult brown anoles or the relatively unbiased expression observed in juvenile brown anoles. We found that adults of the 2 species differed significantly in the strength of sex-biased expression for several key upstream genes in the GH/IGF network, including insulin-like growth factors 1 and 2. However, species differences in sex-biased expression were minor when comparing adult slender anoles to juvenile brown anoles. Moreover, the multivariate expression of the entire GH/IGF network (as represented by the first two principal components describing network expression) was sex-biased for the liver and muscle of adult brown anoles, but not for either tissue in juvenile brown anoles or adult slender anoles. Our work suggests that species differences in sex-biased expression of genes in the GH/IGF network (particularly in the liver) may contribute to the evolution of species differences in sexual size dimorphism.